Political corporate social responsibility: The role of deliberative capacity - Carney, Richard W.; El Ghoul, Sadok; Guedhami, Omrane; Lu, Jane W.; Wang, He (Journal of International Business Studies, 2022)
With an emphasis on deliberative processes that occur between managers and stakeholders, the political corporate social responsibility (PCSR) literature has made important advances to our understanding of CSR activities. However, these contributions have tended to focus exclusively on organizational settings. We contend that an understanding of firm-level CSR is incomplete without considering the interrelations between organizations and the wider socio-political environment. Building on work in comparative politics about formal and informal institutions, we posit that firm-level CSR will rise as the deliberative capacity of political institutions increases. The term deliberative capacity refers to the capacity of political institutions to enable diverse stakeholders to collectively assemble and voice their opinions. Findings from our analysis of 21,941 firm-year observations, comprising 3563 unique firms from 34 countries over the 2005–2017 period, suggest that the deliberative capacity of formal and informal institutions not only enhances firm-level CSR activities independently but also complements the deliberative processes at an organizational level in promoting CSR.